TAP polymorphism in patients with Behçet's disease - González-Escribano, M F; Morales, J; García-Lozano, J R; Castillo, M J; Sánchez-Román, J; Núñez-Roldán, A; Sánchez, B (Annals of the rheumatic diseases, 1995)
OBJECTIVE--To determine if susceptibility to Behçet's disease (BD) is associated with polymorphism of HLA-DRB1, HLA-DQB1, DQB1, and TAP1 and TAP2 genes. METHODS--Fifty eight Spanish BD patients and 116 ethnically matched unrelated healthy subjects were typed at the HLA-DRB1 and HLA-DQB1 loci using polymerase chain reaction/sequence specific oligotyping (PCR/SSO). TAP1 and TAP2 alleles were assigned using amplification refractory mutation system-PCR. RESULTS--TAP1C was absent in BD patients, but was found in 12.1% of control subjects (pcorr < 0.05; relative risk = 0.06). Additionally, a linkage disequilibrium between HLA-DQB1*0501 and TAP2B was observed in BD patients (delta = 0.095, pcorr < 0.02), but not in the control group (delta = -0.0031, p > 0.05). CONCLUSIONS--The complete absence of TAP1C alleles in BD patients may indicate that TAP1 polymorphism is not without some significance in the development of BD. Furthermore, the existence of a linkage disequilibrium between HLA-DQB1*0501 and TAP2B in our patients suggests that the gene conferring susceptibility for BD is inherited as an extended haplotype in the population studied.